Characteristics of Evaluation-Process Biology Learning Tools Based on Conceptual Problem-Based Learning Models to Train Critical Thinking Skills - Herdiyana Fitriani; Taufik Samsuri; Fida Rachmadiarti; Raharjo Raharjo (Postgraduate, University of Mataram, 2022)
Critical thinking skills are very important to learn because it emphasizes how to invite students to find and build their own knowledge so that students can develop life skills and are ready to solve problems faced in everyday life. Critical thinking can be trained by applying learner-oriented active learning. Today the development of science and technology affects almost all human life in various fields. These developments make it easier for humans to access all information. In the world of education, the use of technology is very helpful for educators in developing learning so that educators can package and present material to be more quality and varied. The evaluative-process biology learning tool based on the conceptual-problem-based learning model that was developed is a directed, planned, and systematic effort to control the level of success of the learning process and can be integrated into a learning model syntax that can facilitate critical thinking learning. The purpose of this research is to produce a product in the form of an evaluative-process biology learning device based on a conceptual problem-based learning model to train students' critical thinking skills. This research is development research with specific targets to be achieved in this research, namely to produce evaluative-process biology learning tools based on valid conceptual-problem-based learning models to train students' critical thinking skills with components; Semester Program Plans (SPP), textbooks, Student Worksheets (SW), textbooks, and Critical Thinking Ability Test (CTAT) instruments to measure students' critical thinking skills. The results showed that all the elements that make up the device have been declared valid. The conclusion from the results of this further research can be the foundation for its implementation in the classroom, which is empirically expected to be effective in training students' critical thinking